2018
DOI: 10.1016/j.celrep.2018.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Arrayed Analysis of Protein Degradation Reveals Cellular Targets for HIV-1 Vpu

Abstract: SUMMARY Accessory proteins of lentiviruses, such as HIV-1, target cellular restriction factors to enhance viral replication. Systematic analyses of proteins that are targeted for degradation by HIV-1 accessory proteins may provide a better understanding of viral immune evasion strategies. Here, we describe a high-throughput platform developed to study cellular protein stability in a highly parallelized matrix format. We used this approach to identify cellular targets of the HIV-1 accessory protein Vpu through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…Further, a moderate level of Tetherin antagonism could be selected for if cell-to-cell transmission is enhanced by Tetherin restriction ( Gummuluru et al, 2000 ; Jolly et al, 2010 ), such as is observed for MoMLV in mice ( Liberatore et al, 2017 ). Interestingly, Vpu counteracts UBE2L6 ( Jain et al, 2018 ) which we describe as an inhibitor of both HIV-1 LAI and HIV-1 Q23.BG505 suggesting that Vpu from both viruses are unable to fully counteract UBE2L6 in IFN-treated THP-1 cells.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Further, a moderate level of Tetherin antagonism could be selected for if cell-to-cell transmission is enhanced by Tetherin restriction ( Gummuluru et al, 2000 ; Jolly et al, 2010 ), such as is observed for MoMLV in mice ( Liberatore et al, 2017 ). Interestingly, Vpu counteracts UBE2L6 ( Jain et al, 2018 ) which we describe as an inhibitor of both HIV-1 LAI and HIV-1 Q23.BG505 suggesting that Vpu from both viruses are unable to fully counteract UBE2L6 in IFN-treated THP-1 cells.…”
Section: Discussionmentioning
confidence: 78%
“…MxB, TRIM5alpha, UBE2L6 and IFITM1 are strong hits in both the HIV-1 LAI and the HIV-1 Q23.BG505 screens (cyan in Figure 6B ) suggesting that these ISGs inhibit a range of HIV isolates. UBE2L6 has recently been shown to inhibit HIV in an overexpression assay and is antagonized by Vpu ( Jain et al, 2018 ). In contrast, several other ISGs scored highly in the HIV-1 LAI PIKA HIV screen but not the HIV-1 Q23.BG505 screen including LGALS3BP (also known as 90K or M2BP), SAMD9L and Tetherin/BST2 (dark blue in Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Vif usurps a cellular RING ubiquitin ligase assembled on a Cullin 5 scaffold (CRL5) to antagonize APOBEC3 family cytidine deaminases, which are capable of inducing lethal G-to-A hypermutation in viral cDNA ( 4 ). Vpu hijacks a CRL1 E3 ubiquitin ligase complex to antagonize the CD4 receptor ( 5 ), thereby preventing superinfection, and to deplete select proteins that are involved in interferon-inducible antiviral pathways ( 6 ). Overall, how Vif and Vpu exploit cellular E3 enzymes to facilitate HIV-1 infection is relatively well understood.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 Vif recruits the Cul5/Elongin ubiquitin ligase complex to target APOBEC3 for degradation [96][97][98], while Vpu downmodulates both CD4 and tetherin/BST2 by recruiting a cullin1-Skp1 ubiquitin ligase complex. Recently, it was found that HIV-1 Vpu targets additional ISGs including CD99, PLP2, and UBE2L6 for proteolytic degradation in a manner mechanistically similar to antagonism of BST2 [99][100][101][102]. HIV-1 Vpr and its Vpr/Vpx homologs in HIV-2 and SIV associate with the cullin4A-DDB1-DCAF1 complex to target multiple host factors including tet methylcytosine dioxygenase 2 (TET2) and helicase-like transcription factor (HLTF) for degradation, thus promoting virus infection [103,104].…”
Section: Counteraction Of Hiv-1 Restriction Factorsmentioning
confidence: 99%